Vegetation of the Žale cemetery (Ljubljana) - Šilc, Urban (Hacquetia, 2015)
The paper presents results of a vegetation survey of the cemetery of Ljubljana as a specific urban habitat with a high diversity of vegetation types. Seventeen different plant communities were found, mostly weed (hoe weed and garden communities), trampled and ruderal communities. This indicates frequently disturbed habitat with different microclimatic conditions than those in the surroundings.